Habeas Corpus against Criminal Court Decisions in the Code of Constitutional Procedure - Aguirre Chumbimuni, Javier (2005)
This paper provides an overview of the recent amendment to the Peruvian Code of Constitutional Procedure on the constitutional procedure of habeas corpus in cases of violation, threat or restriction of personal liberty in the context of criminal proceedings. An a contrario sensu interpretation of Law No. 23506 and its complementary law has established that habeas corpus would be applied in the case of irregular procedures, although the law does not explicitly state this. Consequently, in order for habeas corpus to be valid, the irregular procedure had to be directly related to the violation of constitutional guarantees such as due process and effective judicial protection, and this violation had to affect, threaten or limit personal liberty. The absence of an explicit rule led the Code of Constitutional Procedure to state textually that habeas corpus proceedings may be brought against final judicial decisions that manifestly violate individual liberty and effective judicial protection. In this context, the author proposes a legislative amendment that would allow habeas corpus and establish that the final nature of the decision should not be required when: (i) the violation is obvious, unquestionable, obvious and undeniable; (ii) it is impossible to lodge the relevant appeals within the procedure due to an act of God or force majeure; (iii) or if, despite having lodged the appeals, they are not resolved within the period established by law or within a reasonable period of time.